2018
DOI: 10.1093/ofid/ofy031
|View full text |Cite
|
Sign up to set email alerts
|

Palivizumab Prophylaxis for Respiratory Syncytial Virus: Examining the Evidence Around Value

Abstract: Respiratory syncytial virus (RSV) infection is the most common cause of lower respiratory tract infection and the leading cause of hospitalization among young children, incurring high annual costs among US children under the age of 5 years. Palivizumab has been found to be effective in reducing hospitalization and preventing serious lower respiratory tract infections in high-risk infants. This paper presents a systematic review of the cost-effectiveness studies of palivizumab and describes the main highlights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 29 publications
0
53
0
4
Order By: Relevance
“…Currently, RSV vaccines under development are in phase III clinical trials, constituting a step in the right direction . In infants at high‐risk (preterm or having chronic illness), RSV neutralizing monoclonal antibodies, including the FDA‐approved palivizumab, are effective for prophylaxis but remain very expensive in developing countries . The emergence of RSV variants that are resistant to palivizumab is a concern that highlights the need for more therapeutic options .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, RSV vaccines under development are in phase III clinical trials, constituting a step in the right direction . In infants at high‐risk (preterm or having chronic illness), RSV neutralizing monoclonal antibodies, including the FDA‐approved palivizumab, are effective for prophylaxis but remain very expensive in developing countries . The emergence of RSV variants that are resistant to palivizumab is a concern that highlights the need for more therapeutic options .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have found a lower risk for severe RSV‐associated infection than those reported in palivizumab efficacy studies, particularly in otherwise heathy preterm infants, leading to changes in the recommendations for palivizumab administration in the United States . However, questions still remain regarding the optimal approach for RSV prophylaxis with palivizumab, and the need for additional epidemiological data regarding the incidence of RSV hospitalizations has been identified . The incidence of ARI‐ and RSV‐associated hospitalizations varies in different countries .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, questions still remain regarding the optimal approach for RSV prophylaxis with palivizumab, and the need for additional epidemiological data regarding the incidence of RSV hospitalizations has been identified. 11,12 The incidence of ARI-and RSV-associated hospitalizations varies in different countries. [13][14][15][16] This could be the result of diverse factors, including social conditions, environmental factors, or healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
“…Neutralizing antibodies against nCoV 19 surface antigens prevent virus entry of which, S protein considered as a good candidate. These monoclonal neutralizing antibodies provide a passive immunity in the time of exposure like palvizumab as a putative example that has been applied for prevention of RSV infection (92). Anti-inflammatory antibodies like anti IL6 receptor (Tocilizumab) and anti ITGA4 (Natalizumab) may inhibit inflammation and cellular extravasion (101, 102).…”
Section: Monoclonal Antibodies and Recombinant Proteinsmentioning
confidence: 99%